In what ways did the 2014-2015 Ebola Viral Disease outbreak in Sierra Leone affect women? : an examination of gender and human rights in a major disease outbreak - Oakes, David (Massey University, 2015)
Ebola Viral Disease (EBV) is a filovirus with a high mortality rate that ravaged the West African region intensively in the 2014/2015 period, with some cases persisting into 2016. The rapid advance of the illness was characterised by the near collapse of the health system of Sierra Leone, as medical and nursing staff fled or succumbed to the disease. The statistics concerning mortality rates from the illness in West Africa reflect an epidemic in which more women than men have died. These statistics parallel the gendered mortality rates of many natural disasters, and it is clear that epidemics and disasters, when they occur, often reflect pre-existing gender inequalities. This is a fact recognised within the policy structures of many large international NGOs when planning humanitarian response. The reasons for these disproportionate figures are explored within this report using a human rights perspective. This report draws on academic and grey literature, and a small-scale survey of workers involved in caring for those suffering from Ebola, to explore how a person’s level of risk to an event like Ebola and their capacity to respond to or prepare for it, can be affected by a person’s gender, level of poverty, social class, age, ethnicity, and the pre-existing human rights landscape. Human rights are intended to be universal, but as this report will demonstrate, there are many factors limiting the implementation of basic human rights in relation to gender and humanitarian action. This study explores some of the reasons why more women than men died from Ebola in Sierra Leone and why, as many of the survey respondents reported, women suffered disproportionately during the outbreak. The reasons for this are outlined within the findings, but include cultural practices around mortality, gender roles within society, a lack of education leading to an inability to take up preventative health messages, and pre-existing bias against women at many levels of society.